2015
DOI: 10.1111/syen.12135
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeny of sand flies (Diptera: Psychodidae: Phlebotominae), using recent Ethiopian collections and a broad selection of publicly available DNA sequence data

Abstract: Sand flies in the psychodid subfamily Phlebotominae carry important human pathogens in the trypanosomatid protozoan genus Leishmania (Cupolillo). Despite the fact that hundreds of sequences for this group are now publicly available, they constitute different sets of taxa and genetic markers. Integrating these data to construct a molecular phylogeny of the family is a significant bioinformatics challenge. We used sequences of eight markers obtained from freshly collected sand flies from Ethiopia and combined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 80 publications
(112 reference statements)
6
13
0
Order By: Relevance
“…The phylogenetic and sequence analysis showed that most of the S. schwetzi salivary protein sequences are more divergent, compared to the Lutzomyia and Phlebotomus proteins. However, the results of phylogenetic comparison of S. schwetzi salivary protein families (antigen 5-related proteins, lufaxins, YRPs, and apyrases) were in accordance with the established sand fly phylogeny [70,71]. The S. schwetzi OBPs showed high sequence divergence, which is together with high gene duplication rates, typical for the sequences belonging to D7-related and PpSP15-like families [60].…”
Section: Plos Onesupporting
confidence: 71%
See 1 more Smart Citation
“…The phylogenetic and sequence analysis showed that most of the S. schwetzi salivary protein sequences are more divergent, compared to the Lutzomyia and Phlebotomus proteins. However, the results of phylogenetic comparison of S. schwetzi salivary protein families (antigen 5-related proteins, lufaxins, YRPs, and apyrases) were in accordance with the established sand fly phylogeny [70,71]. The S. schwetzi OBPs showed high sequence divergence, which is together with high gene duplication rates, typical for the sequences belonging to D7-related and PpSP15-like families [60].…”
Section: Plos Onesupporting
confidence: 71%
“…Third protein, SschwYRP3, possessed 2 putative O-glycosylation sites and predicted Mw of 43.8 kDa (secreted variant). All sand fly YRPs sequences share similar Cys motif (CX 67-72 CX 122-123 CX [71][72][73][74][75][76] C modified according to [60]). Interestingly this sequence design was modified for all three SschwYRPs-SschwYRP1: CX 64 CX 120 CX 69 C; SschwYRP2: CX 57 CX 114 CX 73 C; SschwYRP3: CX 66 CX 138 CX 73 C (S7 Fig).…”
Section: Yellow-related Proteins (Yrps)mentioning
confidence: 99%
“…However, using a sand fly saliva-based vaccine presents its own challenges. The natural evolutionary pressure that conditioned the speciation of the different Phlebotominae that transmit leishmaniasis 47 , brought as a logical consequence the lower potential for cross-reactivity (due to the known—although not strict—relation between T cell epitopes’ conservation and immunogenicity 48 ). Therefore defined sand fly salivary proteins will have a limited anti- Leishmania vaccine spectrum: effectiveness will probably be limited to the geographical region where the vector species is prevalent, and consequently to the parasite species and disease manifestation associated to that specific vector 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…bergeroti) with poor support. Finally, Grace-Lema et al [ 20 ] used a patchy matrix of 7 genes (65% missing data, ca 45% of the species with more than 85% missing data) to infer a phylogeny of phlebotomine sand flies (113 terminals). However, as for the rest of the tree, relationships between the four species of Paraphlebotomus were poorly resolved.…”
Section: Introductionmentioning
confidence: 99%